Production and quality of tropical grasses at different regrowth intervals in the Brazilian semiarid - Pereira, Genildo Fonseca; Emerenciano Neto, João Virgínio; Difante, Gelson dos Santos; Assis, Liz Carolina da Silva Lagos Cortes; Lima, Patrícia de Oliveira; Santos, Rodrigo da Silva (Acta Scientiarum. Animal Sciences, 2021)
The objective of this study was to evaluate the production and chemical composition of three forage species at different regrowth intervals. A 3 x 4 randomized-block factorial design with three forage species (Andropogon, Buffel, and Massai) and four regrowth intervals (21, 35, 49, and 63 days) was used. There was no interaction (p > 0.05) between forage species and regrowth interval on any of the chemical components evaluated. The crude protein content decreased but the contents of neutral detergent fiber, acid detergent fiber and hemicellulose increased with increasing regrowth interval (p > 0.05). Only the contents of crude protein and ether extract were similar (p > 0.05) among grasses. A significant interaction was observed (p < 0.05) between forage species and regrowth interval on forage mass. Andropogon grass had the highest forage mass at 63 days (3,270.1 kg ha-1 DM cut-1) and the highest productivity regardless of the regrowth interval (19.1 t ha-1 DM year-1). Therefore, Andropogon grass was the most productive forage among the tested species. Pastures should be managed with shorter growth intervals due to the highest crude protein level and the lowest contents of neutral detergent fiber and acid detergent fiber.